(untitled) (International Journal of Engineering and Computer Science, 2014)
Cloud computing is a widely adopting paradigm now days. Primary reason behind more organizations adopting cloud is reduction in cost and dynamic resource allocation. Also various characteristics such as scalability, elasticity, multi-tenancy, pay-per-use approach make cloud computing the most wanted and widely popular paradigm today. But with these characteristics, cloud inherits some serious issues like insider attacks, security, and reliability. Cloud is deeply affected by malicious attacks, for example in 2009 Google was attacked by DOS intrusion that took down services of cloud like Google news, Gmail for several days. So the major focus and challenge is securing cloud because huge amount of users and IT organizations implementing cloud services, this is the reason that gaining large user’s trust is very important. Cloud monitoring helps to properly manage and control these issues in an efficient way. This paper has done a brief analysis of cloud computing, security risks in cloud, and overview of cloud monitoring. Current platforms of cloud monitoring are surveyed based on some evaluation parameters and services. Finally research is outlined for cloud monitoring and attack detection using monitoring.